Mhealth terhadap Manajemen Diri dan Motivasi Pengobatan pada Pasien Hipertensi - Maskur, Ach; Efendi, Ferry; Sari, Dianis Wulan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims at hypertension management, which is very important to improve public health and reduce suffering from chronic diseases with the support of mobile health technology (mHealth). The research method used is a literature review through electronic databases and websites, namely Scopus, PubMed, Science Direct, and ProQuest. The research results show that from 11 research articles, there is primary education based on health care technology or mHealth in the form of voice calls, web-based, and applications that can provide access, assessment, assistance, awareness, ability, and activation where mechanisms are felt regarding the use of mHealth services in supporting their hypertension self-management. In conclusion, patients can monitor their health status and self-management progress in real time thanks to mHealth services, which in turn encourages more self-management as well as mHealth services also provide patients with access to health education and reminders to help with their Blood Pressure (BP) self-management. Keywords: Hypertension, Self Management, Mhealth, Motivation, Public Health Services